Effect of Sodium Hypochlorite Concentration on the Outcome of Full Pulpotomy in Mature Permanent Teeth with Irreversible Pulpitis – A Systematic Review - Aakriti Saini; Amandeep Kaur; Sidhartha Sharma; Vijay Kumar; Amrita Chawla; Ajay Logani (Indian Journal of Dental Research)
To determine the outcome of full pulpotomy in management of mature permanent teeth with irreversible pulpitis when 2.5% versus other concentrations of sodium hypochlorite (NaOCl) were used to achieve haemostasis. Electronic searches were performed in PubMed, Embase, Web of Science, International Clinical Trials Registry Platform, and ClinicalTrials.gov for English language articles until July 2021. Randomised clinical trials and cohort, cross-sectional, and case-control studies where full pulpotomy was performed to manage mature permanent molar teeth with irreversible pulpitis and no periapical radiolucency were included. Newcastle Ottawa Scale and the Cochrane risk of bias tool were used for quality assessment. The success rate for full pulpotomy was documented. The protocol was registered in PROSPERO database (CRD42020177214). Out of 861 studies, four were considered for data analysis. Three studies were single-arm prospective trials on pulpotomy, while one was a randomised control trial comparing pulpotomy and root canal treatment. A combined success rate of 93% from 117 teeth was reported from three studies using 2.5% NaOCl as a haemostatic agent. One study used 5% NaOCl and reported a success rate of 100% (n = 6 teeth). The certainty of evidence substantiated by the GRADE approach was of low quality. Overall quality assessment revealed a considerable risk of bias in three studies. Irrespective of the NaOCl concentration, the success rate of pulpotomy in mature permanent teeth with irreversible pulpitis was high. No study compared the different concentrations of NaOCl as a haemostatic agent. Further, randomised controlled trials are required to investigate the effect of NaOCl concentration for haemostasis on the outcome of pulpotomy.